2019
DOI: 10.7322/jhgd.v29.9425
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of training influence on infant manual behavior: a systematic review

Abstract: Introduction: Researchers have widely investigated how interventions by means of training can improve manual behaviors in infants. However, no systematic review has been found on this topic. Objective: To analyze the quality of scientific evidence considering the methodological quality and level of evidence by type of study in research on training of object-directed manual behaviors in infants in the first 18 months of life. Methods: National Library of Medicine (PubMed/MEDLINE), Latin American and Caribbean H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
2
0
1
Order By: Relevance
“…However, these functions were compromised during the course of the GBS, especially the ability to perform the pinch movement, taking up to 32 days for its full recovery. Nascimento and colleagues, in a recent systematic review, found no studies that analyzed manual function in children up to 18 months of age diagnosed with developmental dysfunction 15 , demonstrating the importance of monitoring this type case study in order to analyze the evolution of this function.…”
Section: Discussionmentioning
confidence: 99%
“…However, these functions were compromised during the course of the GBS, especially the ability to perform the pinch movement, taking up to 32 days for its full recovery. Nascimento and colleagues, in a recent systematic review, found no studies that analyzed manual function in children up to 18 months of age diagnosed with developmental dysfunction 15 , demonstrating the importance of monitoring this type case study in order to analyze the evolution of this function.…”
Section: Discussionmentioning
confidence: 99%
“…o longo do desenvolvimento do lactente, as habilidades motoras, como o alcance manual, sa o adquiridas e aprimoradas. O alcance manual e definido como a habilidade de localizar e tocar o objeto no espaço, por meio de uma trajeto ria realizada por uma ou ambas ma os 1,2 . O iní cio desta habilidade ocorre nos primeiros meses de vida (3-4 meses em lactentes sauda veis), de acordo com a interaça o de fatores, como mudanças no desenvolvimento, aquisiça o de coordenaça o, percepça o das propriedades fí sicas do objeto, força antigravitacional e melhor direcionamento dos membros superiores 3 .…”
Section: Introductionunclassified
“…In this issue, It can be found articles on specific topics that include the development of infants and adolescents [13][14][15][16][17][18][19][20] , including scientific articles focusing on neonatal mortality 19 , clinical conditions of newborns exposed to syphilis 20 malformations of the nervous system 18 , respiratory system 15 and endocrine system 21 resulting in the development of syndromes during their development, as well as articles on infant feeding through maternal colostrum and its composition 13 , including feeding issues 14 and manual behavioral 16 .…”
mentioning
confidence: 99%